Karakteristik Fraksi Aktif Biopigmen Fukosantin Rumput Laut Cokelat sebagai Antioksidan dan UV-protector: Characteristics of Fucoxanthin’s Active Fraction from Brown Seaweeds Biopigments as Antioxidants and UV Protectors - Asadatun Abdullah; Nurjanah Nurjanah; Ade Irma Suryani Nasution (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Padina sp. and Sargassum sp. contains pigment namely fucoxanthins and have antioxidants, anticarcinogenic, and anti-UV. The objectives of this study were to determine the optimal concentration of acetone to produce the best fucoxanthin active fraction with antioxidant, total phenol, SPF value functions as well as to identify the profile of the compound with LC-MS/MS. Seaweeds were immersed in 10% DMSO before extracted with 80% and 90% acetone solvent. The results of antioxidant DPPH, FRAP, and ABTS were Padina sp. of 153.55 ppm, 94.22 μmol Fe2+/g, 66.43 ppm (80% acetone) and 65.76 ppm, 93.11 μmol Fe2+/g, 78.33 ppm (90% acetone); Sargassum sp. of 131.37 ppm, 103.67 μmol Fe2+/g, 57.29 ppm (80% acetone) and 103.24 ppm, 71.72 μmol Fe2+/g, 61.45 ppm (90% acetone). Total phenol of 80% dan 90% acetone from Padina sp. were 675.48 mg GAE/g and 852.90 mg GAE/g; Sargassum sp. of 565.81 mg GAE/g and 135.16 mg GAE/g. SPF value with optimal concentration 50 mg/mL had resulted of Padina sp. by 9.08 (80% acetone) and 17.10 (acetone 90%); Sargassum sp. of 7.56 (acetone 80%) and 3.56 (acetone 90%). Acetone 80% is the optimal solvent to produce the best fucoxanthin active fraction with the highest characteristics of yield, antioxidant activity, total phenol content, and SPF value.